2003
DOI: 10.1016/j.ecoleng.2003.12.004
|View full text |Cite
|
Sign up to set email alerts
|

How hydrological and hydraulic conditions affect performance of ponds

Abstract: During the 1990s there has been a growing interest in (re)constructed wetlands and ponds for treatment of agricultural runoff, sewage water, and stormwater. Some of these facilities, however, are poorly designed in terms of hydrological and hydraulic performance, which strongly affects their treatment capacity. This paper gives an overview of the present knowledge regarding pond hydraulics in terms of effective volume ratio and dispersion. The importance of these parameters is demonstrated by modelling of nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(79 citation statements)
references
References 12 publications
(15 reference statements)
1
70
0
2
Order By: Relevance
“…189 190 191 192 193 194 195 196 197 198 The volume of the water compartment and the number of serial reactors were defined to represent the measured hydraulic behaviour of the Lilla Essingen pond. Persson and Wittgren (2003) and Jansons et al (2005) estimated a 位 value around 0.9 for a pond with similar layout. The eight-reactor configuration which was adopted to simulate the Lilla Essingen pond ensured a 位 equal to 0.88.…”
Section: Mp Fate Modelsmentioning
confidence: 92%
“…189 190 191 192 193 194 195 196 197 198 The volume of the water compartment and the number of serial reactors were defined to represent the measured hydraulic behaviour of the Lilla Essingen pond. Persson and Wittgren (2003) and Jansons et al (2005) estimated a 位 value around 0.9 for a pond with similar layout. The eight-reactor configuration which was adopted to simulate the Lilla Essingen pond ensured a 位 equal to 0.88.…”
Section: Mp Fate Modelsmentioning
confidence: 92%
“…-Hydrology and hydraulic design of the wetland (Kadlec, 1989;Owen, 1995;Persson and Wittgren, 2003).…”
Section: Previous Workmentioning
confidence: 99%
“…It has been found that wetlands are efficient in removing fecal colliforms, BOD, COD, and TSS (all around 90%) although showing low efficiency in NH 3 -N (50-60%), and P (25-45%) removal (Juwarkar et al, 1995;Kantawanichkul et al, 1999;Platzer, 1999;Manios et al, 2003;Mbuligwe, 2005;Steer et al, 2005). However, high removal rate of BOD, COD is influenced by organic loading rate (Persson and Wittgren, 2003). With high loading rate, removal efficiency of BOD, and COD can even decrease to 70%.…”
Section: Previous Workmentioning
confidence: 99%
“…Waste removal efficiencies in these systems are highly dependent on hydraulic performance [15], and unsatisfactory hydraulic control is one of the main factors contributing to poor pond performance, especially after years of operation [16]. WSPs are notoriously hydraulically inefficient, and pond hydraulics are further compromised by sludge accumulation and distribution over time [17].…”
Section: Introductionmentioning
confidence: 99%